Marphological variation in the dusky fruit bat, penthetor lucasi, in Sarawak, Malaysia - Mohd. R., Abd. Rahman (Chulalongkorn University, 2010)
Morphological analysis of 70 adult individuals of the dusky fruit bat, Penthetor lucasi, was performed using 15 external characters and 18 craniodental characters. Multiple regression and discriminant function analysis (DFA) were applied to test the effects of sex, location and interaction between individuals in the study, and to determine and identify characters which are efficient in differentiating individuals among populations, respectively. Most characters were significantly affected by sex, locality and their interactions. Thus, separate analyses were done for both sexes. The fourth digit metacarpal length (D4MCL) and bulla length (BL) of males, and the hind foot (HF) and dental length (DL) of females, were suggested as the best predictors for the external and craniodental characters, respectively, in differentiating P. lucasi from different localities. These findings establish the morphological morphological variation between three geographically separate populations of P. lucasi within Sarawak. It is suggested that different ecological forces between populations, such as breeding, foraging behaviour, crowding effects and resource availability, could have been the moulding factors behind the observed morphological variations in the different P. lucasi populations.